Differential expression of circulating Th1/ Th2/ Th17 cytokines in serum of Chlamydia trachomatis-infected women undergoing incomplete spontaneous abortion. (September 2017) - Prasad, Priya; Singh, Namita; Das, Banashree; Raisuddin, Sheikh; Dudeja, Mridu; Rastogi, Sangita
Abstract: The study aimed to elucidate role of Th1/Th2/Th17 cytokines in the immunopathogenesis of spontaneous abortion in Chlamydia trachomatis (Ct)-positive first-trimester aborters. Endometrial curettage tissue and serum were collected from 145 aborters (spontaneous abortion (SA) group, n = 85; recurrent miscarriage (RM) group, n = 60) and 120 controls attending Department of Obstetrics & Gynecology at Safdarjung hospital, New Delhi (India). Polymerase chain reaction was used to detect Ct plasmid/MOMP, while commercial cytometric bead array kit was utilized to estimate circulating serum cytokines. 13.7% aborters were Ct-positive, however, none was found to be infected among controls. IFN-γ, TNF-α, IL-2, IL-6 and IL-17A cytokines were significantly increased in SA group/RM group (Ct-infected) versus controls. IL-4 showed no difference between groups, while IL-10 was significantly elevated in controls versus Ct-infected subjects in SA group/RM group. Furthermore, IFN-γ, TNF-α, IL-6, IL-17A cytokines were significantly elevated in Ct-positive RM group versus Chlamydia -infected SA group. However, IL-2, IL-4 and IL-10 cytokines showed no significant difference between Ct-positive SA group versus infected RM group. Positive correlation was found between few cytokines (TNF-α and IFN-γ/IL-17A; IL-17A and IFN-γ/IL-6) in Ct-positive aborters. Our study clearly established the role of Th1/Th2/Th17 cytokines in the pathogenesis of spontaneous abortion in Ct-infected subjects and found that Chlamydia -positive recurrent aborters had a predominant Th1/Th17 bias. Highlights: Role of cytokines in pathogenesis of C. trachomatis -induced spontaneous abortion. Positive correlation between IL-6/IL-17A cytokines in Chlamydia -positive aborters. A predominant Th-1/Th-17 bias observed in Chlamydia -infected recurrent abortion.